Analisis Strategi Guru dalam Pelaksanaan Pengelolaan Kelas pada Pembelajaran IPAS di Sekolah Dasar: Penelitian - Nur Fadilah Nasution; Alpidsyah Putra; Inge Ayudia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to explore the strategies applied by teachers in managing classes in IPAS learning at SDN 1 Langsa. The subjects in this study were teachers who taught IPAS subjects at SDN 1 Langsa. This research uses a qualitative descriptive approach. Data collection techniques were carried out through observation sheets, interviews, and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, conclusions, and verification. Based on the results of the research that has been conducted, the classroom management strategy in IPAS learning applied by class IV B, V B, and VI B teachers at SDN 1 Langsa is the teacher's strategy in classroom management is that teachers, especially those who teach IPAS at SDN 1 Langsa, use differentiated learning strategies and discuss with students through questions and answers, arrange student seating once a month, conduct games, classroom m anagement through.